Human resources for the control of road traffic injury - Mock Charles; Kobusingye Olive; Anh Le Vu; Afukaar Francis; Arreola-Risa Carlos (The World Health Organization, 2005)
The definition of the ideal numbers and distribution of human resources required for control of road traffic injury (RTI) is not as advanced as for other health problems. We can nonetheless identify functions that need to be addressed across the spectrum of injury control: surveillance; road safety (including infrastructure, vehicle design, and behaviour); and trauma care. Many low-cost strategies to improve these functions in low- or middle-income countries can be identified. For all these strategies, there is need for adequate institutional capacity, including funding, legal authority, and human resources. Several categories of human resources need to be developed: epidemiologists who can handle injury data, design surveillance systems, and undertake research; engineers and planners versed in safety aspects of road design, traffic flow, urban planning, and vehicle design; police and lawyers who understand the health impact of traffic law; clinicians who can develop cost-effective improvements in the entire system of trauma treatment; media experts to undertake effective behaviour change and social marketing; and economists to assist with cost-effectiveness evaluations. RTI control can be strengthened by enhancing such training in these disciplines, as well as encouraging retention of those who have the needed skills. Mechanisms to enhance collaboration between these different fields need to be promoted. Finally, the burden of RTI is borne disproportionately by the poor; in addition to technical issues, more profound equity issues must be addressed. This mandates that people from all professional backgrounds who work for RTI control should develop skills in advocacy and politics.